A New Protection System to Avoid Major Bleeding at Puncture Site-Results from the First in Men Study - Noory, Elias; Beschorner, Ulrich; Zeller, Thomas; Böhme, Tanja (Cardiology and Cardiovascular Medicine, 2020)
Background: The use of catheter-directed thrombolysis (CDT) is an effective option for the treatment of acute lower limb ischaemia, but has a high complication rate. Systemic bleeding and bleeding at the puncture site are particularly dreaded. Purpose: To evaluate the safety and effectiveness of the new vascular access protection system CaveoVasc® protection system in patients undergoing CDT. Materials & Methods: The prospective, single-center single-arm CaveoVasc® study enrolled 20 patients with critical limb ischaemia (CLI) requiring treatment with CDT. Primary safety endpoint was the rate of all major bleedings (BARC > type 3) from the start to the end of the CDT procedure. Secondary safety endpoints were bleedings (BARC ≥ 1 and BARC ≥ 2) and adverse events at discharge and at 30 days. The primary performance endpoint was length of CDT. Secondary performance endpoints were the rate of subjects completing the CDT without early interruption due to access site complication, the rate of successful thrombolysis without bleeding complication and pain at access site. Results: Twenty patients with CLI requiring treatment with CDT were enrolled. No major bleeding occurred at the access site. The CDT treatment continued for a mean of 16.5+/- 5.2 hours without interruption due to bleeding complications at the access site. In 5 cases minor bleeding (classified as BARC 1 and BARC 2) was documented but only two of these patients had a bleeding at the site of the puncture during the procedure. In 18 cases (94.7%) the CDT procedure was completed successfully and without early interruption. At the start of the CDT, the average pain score was 0.3 ± 1.1, 2.0 ± 2.3 after 6 hours, and 0.8 ± 2.0 at the end of the CDT procedure. Twelve adverse events had occurred by the 30 day-visit. Conclusion: The stud